37.9k views
3 votes
I'm kinda stumped on this

Solve -4x + x = - 9/4

1 Answer

3 votes

Answer:

x = 3/4

Explanation:

It usually works well to collect terms first. (Add the coefficients of x.)

-4x +x = -9/4

(-4+1)x = -9/4

-3x = -9/4 . . . . . . equation with terms collected

Now, you can divide by the coefficient of x. Here, it can be useful to consider this to be the same as multiplying by the inverse of that coefficient, which inverse is -1/3.

(-1/3)(-3x) = (-1/3)(-9/4) . . . . . multiply both sides by -1/3

x = 3/4 . . . . . simplify

User Emilio Martinez
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.